Nurses’ knowledge and practices regarding prevention and management of pressure ulcer for hospitalized patient (Asian Journal of Medical and Biological Research, 2020)
Pressure ulcers have been labelled as one of the most expensive and physically debilitating complications in the 20th century. After cancer and heart diseases pressure ulcers are the third most expensive disorder. Several studies have indicated that nurses' knowledge and practices about pressure ulcer prevention and management are inadequate. This is a descriptive co-relational study aimed to assess nurses‟ knowledge and practices related to pressure ulcer prevention and management. It also examines the relationships between nurses‟ knowledge and practice with respect to pressure ulcer prevention and management. The subjects were nurses working at Rajshahi Medical College Hospital. Three hundred nurses were selected for this study, two hundred and ninety four nurses were completed the questionnaire and response rate was 98%. Three tools were used for data collection: Demographic, Knowledge and Practice questionnaire. Data were analysed by descriptive and Pearson product-moment correlation statistics. The findings showed that nurses had a moderate level of knowledge and a moderate level of practice when we categorized the findings according to their age, working experience and educational level they scored low level of knowledge. There was a significant correlation was found between nurses knowledge and practice regarding pressure ulcer prevention and management (r =.136, p>.05). Findings of the present study suggest that nurses need to increase knowledge on pressure ulcer prevention and management in order to improve nursing practice in this.Asian J. Med. Biol. Res. June 2020, 6(2): 237-243